The Time Course of Development and Impact From Viral Resistance Against Ganciclovir in Cytomegalovirus Infection. Issue 2 (2nd January 2013) - Cunha‐Bang, C. da; Kirkby, N.; Sønderholm, M.; Sørensen, S. S.; Sengeløv, H.; Iversen, M.; Rasmussen, A.; Gustafsson, F.; Frederiksen, C. M.; Kjær, J.; Lepri, A. Cozzi; Lundgren, J. D.
Abstract : (Val)ganciclovir is used to treat cytomegalovirus (CMV) infection following solid organ (SOT) or hematopoietic stem cell (HSCT) transplantation. Treatment failures occur, but the contribution from 39 known ganciclovir‐related mutations (GRMs) in the CMV‐UL97 gene remains controversial. We propose a categorization of these GRMs potentially useful when interpreting sequence analyses in clinical settings. The UL97 gene was sequenced from first/recurrent CMV infections among consecutive SOT or HSCT recipients during 2004–2009. GRMs were categorized as: Signature GRM (sGRM) if in vitro ganciclovir IC50 ratio for mutated versus wild‐type virus >2 (n = 24); polymorphic GRM (pGRM) if ratio <2 (n = 15). (Val)ganciclovir treatment failure was defined as persistent viremia for 30 days or switch to foscarnet within this period. Of 99 (49 HSCT and 50 SOT) recipients with one CMV infection episode, 15 (13 HSCT and 2 SOT) experienced a total of 19 recurrent infection episodes. The prevalence of sGRM was 0% at start of first episode, whereas at start of recurrent episodes, prevalence was 37%. Only one sGRM was present at a time in individual patients. Patients with CMV containing an sGRM (vs. wild type)—but not with a pGRM—were at excess risk of treatment failure (odds ratio = 70.6 [95% CI:8.2–609.6]; p < 0.001). sGRMs emerged only following longer termed use of antiherpetic drugs and usually in recurrent CMV infection episodes. Risk of ganciclovir treatment failure was raised if an sGRM was detected. Abstract : Following sequence analyses of CMV UL97, treatment response to (val)ganciclovir was analyzed in episodes of posttransplant CMV infection, and the odds ratio of treatment failure was found to be significantly higher in episodes of infection where a signature ganciclovir‐related mutation was found versus episodes of infection with only wild‐type virus.